Faktor-Faktor Yang Mempengaruhi Generasi Y Dan Z Dalam Niat Berinvestasi Di Fintech - Shofi Justitia; Lia Febria Lina; Dian Novita (JEMBATAN, 2022)
ABSTRACT : Globally, fintech is growing rapidly, fintech services have become indispensable and become the application of new technology with greater market potential. The development of financial technology provides facilities for investors to invest easily. This study aims to examine and analyze whether perceived convenience, perceived benefits, perceived return and investment knowledge have a positive effect on the intentions of generations y and z in investing online. This study uses quantitative research using primary data and using the Statistical Package for the Social Sciences (SPSS 25.0) to analyze the data that has been collected. The results showed that the intention of generations y and z in investing is influenced by the perception of return and investment knowledge. The findings in this study prove that users are more likely to determine the return they get when investing and have investment knowledge. In terms of technology factors, perceived convenience and perceived benefits of investment applications do not have a positive effect on the intentions of generations y and z in investing online.Keywords: Perceived Ease of Use, Perceived Usefullnes, Perceived Return, Investment Knowledge. ABSTRAK : Fintech secara global berkembang pesat, layanan fintech telah menjadi sangat diperlukan dan menjadi aplikasi teknologi baru dengan potensi pasar yang lebih besar. Perkembangan financial technology memberikan fasilitas bagi para investor untuk dapat berinvestasi dengan mudah. Penelitian ini bertujuan untuk menguji dan menganalisis apakah persepsi kemudahan, persepsi manfaat, persepsi return dan pengetahuan investasi berpengaruh positif pada niat generasi y dan z dalam berinvestasi online. Penelitian ini menggunakan penelitian kuantitatif dengan menggunakan data primer dan menggunakan Statistical Package for the Social Sciences (SPSS 25.0) untuk menganalisis data yang telah terkumpul. Hasil penelitian menunjukkan bahwa niat generasi y dan z dalam berinvestasi dipengaruhi oleh persepsi return dan pengetahuan investasi. Temuan dalam penelitian ini membuktikan bahwa pengguna cenderung lebih menentukan keuntungan (return) yang didapat ketika berinvestasi dan memiliki pengetahuan investasi. Dari sisi faktor teknologi, persepsi kemudahan dan persepsi manfaat pada aplikasi investasi tidak berpengaruh positif terhadap niat generasi y dan z dalam berinvestasi online.Keywords: Persepsi Kemudahan, Persepsi manfaat, Persepsi Return, Pengetahuan Investasi.